Tibialis Anterior Reconstruction With Hamstring Autograft Using a Minimally Invasive Approach. (May 2018) - Karnovsky, Sydney C.; Desandis, Bridget; Papson, Andrea K.; O'Malley, Quinn; DiGiacomo, Robert; O'Malley, Martin J.; Cabe, Taylor N.; Drakos, Mark C.
Background: Tibialis anterior tendon ruptures are rare and can cause significant dysfunction. Often, conservative measures are prescribed because of the morbidity of a tendon transfer as an operative solution. We present a novel reconstruction technique using hamstring autograft, which may obviate the need for local tendon transfer and long-term bracing. Methods: Patients who underwent tibialis anterior reconstruction with hamstring autograft between 2011 and 2015 were screened for inclusion. Eight were included. Functional outcomes were assessed pre-and-postoperatively using the Foot and Ankle Outcome Score (FAOS), Visual Analog Pain Scale (VAS), and Short-Form-12 (SF-12) general health questionnaire. Isokinetic testing using a dynamometer (Biodex System 4 Pro) was performed at 60 and 120 degrees/s, respectively, for inversion/eversion and plantarflexion/dorsiflexion on both ankles at a minimum of 6 months postoperatively to determine peak torque, average power, and total work. Range of motion (ROM) testing was also performed, using a goniometer, at a minimum of 6 months postoperatively. Average follow-up was 17.3 (6.0-40.0) months for strength testing and ROM testing, and 18.5 (12.0-26.0) months for functional outcome scores. Results: Average postoperative functional scores improved for all tests. ROM was similar between the uninvolved and involved ankles for inversion/eversion and plantarflexion/dorsiflexion. Patients showed deficits in dorsiflexion strength in all measures tested and improvements in inversion strength. All patients were able to ambulate without a brace. Conclusion: Use of a hamstring autograft for tibialis anterior reconstruction resulted in good clinical outcomes. This procedure successfully restored ankle ROM postoperatively and tendon strength in inversion and dorsiflexion, with most patients showing little deficit when comparing their involved and uninvolved sides. Level of Evidence: Level IV, Case series.